The Resilience and Lived Experiences of the Parents of Children With Autism in India: A Mixed-method Study - Minitta Maria Regy; Vijaya Lakshmi; Deepthi N Shanbhag (Function and Disability Journal, 2024)
Background and Objectives: Families dealing with autism spectrum disorder (ASD) children try to adapt with different strategies. 1) To assess the resilience of parents dealing with children having ASD and its associated factors. 2) To explore the perspective and strategies of families dealing with children having ASD Methods: This was a mixed-methods study done over a period of 3 months among parents having children diagnosed with ASD; undergoing institutional therapy for more than 6 months in duration. Data collection was done using the PREQ questionnaire and key informant interviews (KII). Informed consent was taken prior to each interview and audio recordings. Relevant tests of significance and deductive analysis followed. Results: There was an equal divide observed between the low (50%) and high resilience (50%) groups. Binary logistic regression showed that the upper socio-economic class showed higher odds of better resilience (OR=4.038, 95% CI, 2.857%, 4.894%) as compared to the lower socio-economic class, and those with higher levels of education showed better resilience (OR=9.903, 95% CI, 2.502%, 3.483% than the lesser educated. KII explored different perspectives on personal experiences, concerns, challenges, attitudes, etc. where both perspectives such as benefits and hardships were addressed on an individual as well as a family basis, respectively Conclusion: Education and socio-economic backgrounds played a role in mending the resilience and other active measures such as peer support mechanisms and self-coping strategies also influenced the attitude and improved determination of parents dealing with children having ASD.